INVESTIGATING THE ANTIOXIDANT EFFECT OF VITAMIN E AGAINST MSG INDUCED OXIDATIVE STRESS ON OVARIES OF WISTAR ALBINO RATS.: JPUMHS; 2025:15:01,64-70. http://doi.org/10.46536/jpumhs/2025/15.01.597 - Piriha Abbasi1, Raima Kalhoro2, Roomi Memon3, Safiya4, Sana Kashif5, Farzana6. , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: MSG, a flavoring agent is well known for its toxic effects on reproductive system due to its oxidative stress which may leads to infertility. Antioxidants like Vit E helps to overcome this issue. OBJECTIVE: To evaluate the toxic effects of MSG on the ovaries of Albino Wistar rats and the possible protective effects of vitamin E on damaged ovarian tissues. STUDY DESIGN: Experimental study. PLACE OF STUDY: The study was performed at the Animal House department, Sindh Agriculture University Tandojam and, the department of Anatomy and Postgraduate laboratory of Isra University Hyderabad. DURATION OF STUDY: 6 months. MATERIALS AND METHODS: 40 Albino Wistar rats were divided into 4 groups. Among them first was controlled group, second was treated with 0.08mg/g of MSG daily, third and fourth were treated with Vit E in the dosage of 0.4mg/g for 30 and 15 days respectively. After a month the animals were sacrificed and slides of 4-6 µm of thickness were made for examination. Spss version 21. and MS Excel was used, chi-square test was applied at the P value of <0.05. RESULTS: The results show that Group A shows no sign of damage, Group B shows hemorrhage, atretic follicles, vacuolation, distorted basement membrane, hypertrophied theca cells, and less mature follicles while Group C shows a marked reduction in all of this damage whereas Group D shows improved results on all of these toxic effects other than vacuolation and atretic follicles. CONCLUSION: MSG causes damage to ovarian tissue and contrary to this Vit E shows a protective effect against this damage.